2013
DOI: 10.4103/2277-9531.119040
|View full text |Cite
|
Sign up to set email alerts
|

Objective structured practical examination as a tool for the formative assessment of practical skills of undergraduate students in pharmacology

Abstract: Introduction:Assessment for practical skills in medical education needs improvement from subjective methods to objective ones. An Objective Structured Practical Examination (OSPE) has been considered as one such method. This study is an attempt to evaluate the feasibility of using OSPE as a tool for the formative assessment of undergraduate medical education in pharmacology.Materials and Methods:Students of second year MBBS, at the end of the first term, were assessed by both the conventional practical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 6 publications
1
29
1
Order By: Relevance
“…No comments were made on the agreement between the two methods, but the plot is clearly showing the disagreement between the two methods. However, contrary to our findings, Malhotra et al have shown that the two methods are in agreement with each other [4].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…No comments were made on the agreement between the two methods, but the plot is clearly showing the disagreement between the two methods. However, contrary to our findings, Malhotra et al have shown that the two methods are in agreement with each other [4].…”
Section: Discussioncontrasting
confidence: 81%
“…In the conventional practical examination (CPE), the examiner does not observe the student in performing the practical, which mostly extends over a long time: Students are evaluated by noting only the final result of the experiment, and the marks awarded vary markedly from one examiner to the other. In OSPE, the practical is performed in the presence of the examiner, who evaluates the psychomotor skills of the students with reference to a checklist; it is therefore based entirely on the student's performance with little scope for subjectivity [4,5]. Despite its drawbacks, the conventional system of practical evaluation holds sway even today in most of the medical colleges in India.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research shows that the type of assessment method adopted can influence student learning. [91011] Considering these facts, we introduced OSPE as a method of learning and evaluation tool for assessment of practical skills in pharmacology examinations for undergraduate students. The method was compared with the conventional method of assessment that is commonly used in India.…”
mentioning
confidence: 99%
“…[12] However, other studies have reported no significant difference between the scores obtained in conventional practical examination and that obtained in OSPE. [13,14] …”
Section: Gram Staining In Microbiology For Second-year Mbbs Students:mentioning
confidence: 99%